Association between Food Choice, Consumption Pattern, Nutritional Status, and Stress among The First-Year University Students in Surabaya - Ayu Christien Lucia Radjah; Emyr Reisha Isaura; Siti Rahayu Nadhiroh (Media Gizi Kesmas, 2022)
Background: The trend of food types has transitioned during the Covid-19 pandemic. The food transition trend affects all people, including the first-year students at university. The food transition is a basic of the diet pattern transition process. Students are obligated to study from home during the pandemic, which means they are more likely to sit in front of the screen. Meanwhile, the pandemic is related to the disturbance of mental health outcomes such as stress.   Objectives: This study was aimed to determine the relationship between food choices and consumption pattern, nutritional status, and stress among the first-year university students in Surabaya. Methods: This research used a cross-sectional design with a sample of 123 first-year university students. Sampling using a simple random sampling method. Data was collected by self-reported online questionnaire including variables of respondents' characteristics, reason food choices, consumption pattern (score and level consumption of foods), nutritional status (body weight and height), and stress. Collected data were analyzed using the Chi-Square Test.  Results: The results showed that respondents who reported stress were 13 (10.57%) students. Our study found that the food choices (e.g., health and convenience) (p = 0,007- 0.016), score of consumption of carbohydrates (p = 0,016) are significantly different between the one who reported stress and the one who did not report any stress.Conclusions: The stress reduction management could be optimized by awareness of the macronutrient intake control to prevent overweight among university students.